ANALISIS KOMUNIKASI MELALUI TEORI RELATIONSHIP: (Studi Kasus Toxic Relationship pada Pasangan Suami Istri Yang Bercerai) - SELVI SOFIAWATI; Wulan Dwi Pratiwi; Selvy Maria Widuhung (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This research is motivated by the researchers' concern about the phenomenon of high divorce rates and declining marriage rates currently, where the aim of this study is to analyze how this phenomenon occurs by examining the communication that takes place in the marriages of today's society, where toxic relationships exist. This research analyzes using Relationship Theory, which investigates two phases: (1) Relationship Formation Phase and (2) Relationship Maintenance Phase. The research employs a descriptive qualitative method, using in-depth interviews to address questions from the theory applied, and the researcher also conducts observations both directly and digitally. The results of this research show that based on Relationship Theory, which describes how a relationship is formed based on the way partners interact, both phases have been experienced, but the maintenance phase could not be successfully navigated due to the presence of a toxic relationship in that phase, leading to divorce. Keywords: Relationship Theory, Toxic Relationship, Maried Couple, Divorced